2008
DOI: 10.1016/j.jbiomech.2007.11.027
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of microtopography and cyclic strain on vascular smooth muscle cell orientation

Abstract: Cellular alignment studies have shown that cell orientation has a large effect on the expression and behavior of cells. Cyclic strain and substrate microtopography have each been shown to regulate cellular alignment. This study examined the combined effects of these two stimuli on the alignment of bovine vascular smooth muscle cells (VSMCs). Cells were cultured on substrates with microgrooves of varying widths oriented either parallel or perpendicular to the direction of an applied cyclic tensile strain. We fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 20 publications
(28 reference statements)
3
31
0
Order By: Relevance
“…Vascular smooth muscle cell (VSMC) coverage is more pronounced on arteries and circumferential alignment of these cells (perpendicular to the direction of blood flow) is likely to maximize structural support given to the endothelium [29][30][31]. Certain smooth muscle differentiation markers, like the protein smoothelin which also directly contributes to contractility, are expressed in VSMCs of perinatal arteries but not in veins [32,33].…”
Section: Cellular Processes Contribution To Av Differentiationmentioning
confidence: 99%
“…Vascular smooth muscle cell (VSMC) coverage is more pronounced on arteries and circumferential alignment of these cells (perpendicular to the direction of blood flow) is likely to maximize structural support given to the endothelium [29][30][31]. Certain smooth muscle differentiation markers, like the protein smoothelin which also directly contributes to contractility, are expressed in VSMCs of perinatal arteries but not in veins [32,33].…”
Section: Cellular Processes Contribution To Av Differentiationmentioning
confidence: 99%
“…Various approaches have been developed to align cells, including topographical pattern (e.g., microgrooves), 16,17 mechanical stimulation (e.g., shear stress, 11 cyclic tension, and combined stimulation), 20 electrical stimulation, 21 and bioprinting. [22][23][24][25][26][27] Quantification of cellular alignment is necessary to validate the effectiveness of these approaches and the engineered microenvironment.…”
Section: Introductionmentioning
confidence: 99%
“…Although quantification of cellular alignment by measuring its physical consequences (e.g., mechanical anisotropy or polarization of infrared light) have been achieved before, 28 this is generally performed in the laboratories primarily by analyzing microscope images using manual measurements 29,30 or automated methods. 11,31,32 Although manual measurement is reliable, 33 it suffers from several limitations: (i) it is tedious and time consuming, (ii) the processing efficiency is low especially when multiple images with hundreds of cells are needed to be processed, and (iii) it has interoperator variability.…”
Section: Introductionmentioning
confidence: 99%
“…The modulation of cellular behavior and differentiation by soluble factors, 15,[36][37][38][39] surface chemistry, [40][41][42][43][44] and biophysical attributes of the extracellular microenvironment [45][46][47][48] has been well established. While, the majority of studies have investigated only one type of biophysical or chemical cue in isolation, a limited number have explored the interaction between multiple biophysical cues, 11,49 surface chemistry, 19,50 or soluble cytoactive factors. 15 Here we have demonstrated that the simultaneous presentation of substratum topographic cues and surfaceassociated biochemical cues potently modulated cellular behavior.…”
Section: Discussionmentioning
confidence: 99%